1979
DOI: 10.1002/aic.690250113
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer in regular arrays of hollow fibers in countercurrent dialysis

Abstract: trol valve pi qc = output of controller q h qi q s qv S Ti To V2 V, LJTERATURE CITED Fussell, J. B., and W. E. Vesely, "A New Methodology for Obtaining Cut Sets for Fault Trees," Trans. Am. Nucl. SOC., 15, 262 ( 1972). Fussell, J. B., "Synthetic Tree Model-A Formal Methodology for Fault Tree Construction," ANCR-1098, Available from = actuating pressure of cooling water control valve = material gow rate to heat exchanger = inflow rate of material to be cooled = output of temperature sensor = flow rate of coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Some of the possible causes include irregularity of fiber spacing, polydispersity of fiber diameter, movement of hollow fiber during operation, influence of the module, and effects of inlet and outlet. The effects of hollow fiber distribution and packing density on mass-transfer performance have been abundantly reported in the literature (Bao et al, 1999;Costello et al, 1993;Crowder and Cussler, 1997;Noda and Gryte, 1979;Wu and Chen, 2000). However, there is little literature on the effect of the inlet and outlet configuration upon mass-transfer performance of the artificial kidney.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the possible causes include irregularity of fiber spacing, polydispersity of fiber diameter, movement of hollow fiber during operation, influence of the module, and effects of inlet and outlet. The effects of hollow fiber distribution and packing density on mass-transfer performance have been abundantly reported in the literature (Bao et al, 1999;Costello et al, 1993;Crowder and Cussler, 1997;Noda and Gryte, 1979;Wu and Chen, 2000). However, there is little literature on the effect of the inlet and outlet configuration upon mass-transfer performance of the artificial kidney.…”
Section: Introductionmentioning
confidence: 99%
“…The complex inlet and outlet configuration and transverse flow cause difficulties of discussing the overall mass transfer performance theoretically. Therefore, most reports in the literature focused on the middle portion of dialyzers (Bao et al, 1999;Costello et al, 1993;Crowder and Cussler, 1997;Jaffrin et al, 1990;Noda et al, 1979). In fact, the configuration of the inlet and outlet seriously affects the velocity field within the artificial kidney, so the clearance is substantially affected.…”
Section: Introductionmentioning
confidence: 99%
“…The increases in fiber length and fiber radius improve the rate of removal of all solutes from blood due to longer residence time of the blood in the dialyzer. Noda and Gryte 28 found that the overall mass transfer coefficient is not only a function of the membrane thickness, membrane type, and nature of the solute but it is also influenced by the packing density of the hollow fibers in the dialyzer shell. Their calculations show that there is an optimal packing density of the fibers.…”
Section: Whole Body Clearancesmentioning
confidence: 99%
“…In a few studies, simultaneous mass and momentum transfers in both radial and axial directions through the dialyzer are taken into account. 26, 28 Noda and Gryte 28 expressed the fluid velocity through the inside of a hollow fiber by that of the parabolic Poiseuille flow, while the velocity profile for the flow through the outside of the fiber was obtained from the literature. In their model, it is assumed that the shape of the cross-sectional concentration profile is constant throughout the major part of the dialyzer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation